The genome sequence of a beetle, Brachypterus glaber (Newman, 1834) [version 1; peer review: 2 approved] - Michael F. Geiser; Talay Namintraporn; Freya Read; Maxwell V.L. Barclay (Wellcome Open Research)
We present a genome assembly from an individual female specimen of Brachypterus glaber (beetle; Arthropoda; Insecta; Coleoptera; Kateretidae). The genome sequence has a total length of 648.30 megabases. Most of the assembly (95.55%) is scaffolded into 11 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled and is 21.86 kilobases in length. Gene annotation of this assembly on Ensembl identified 23,733 protein-coding genes.